GROW-Based Academic Supervision Strategy as a Solution to Improve Learning Quality in Junior High Schools - Raudhatul Hayati; Niswanto; Suparta Rasyid; Junaidah Junaidah (Journal of Education Reseach and Evaluation, 2026)
The implementation of academic supervision in junior high schools has not fully contributed to improving instructional quality, as it remains largely administrative and insufficiently reflective. This condition has limited the optimal development of teachers’ pedagogical competencies in lesson planning, instructional implementation, and learning evaluation. This study aims to analyze, evaluate, and synthesize the application of the GROW (Goal, Reality, Options, Will) model in academic supervision as a strategy for enhancing instructional quality in junior high schools. This research employed a descriptive qualitative approach with a case study design. The participants included the principal, vice principal, teachers, and students of a junior high school, involving eight teachers, several students, and school leaders as key informants. Data were collected through in-depth interviews, classroom observations, and document analysis, using interview guidelines, observation sheets, and instructional planning and evaluation documents as research instruments. The data were analyzed using thematic analysis, involving transcription, coding, categorization, and theme development to identify patterns in the implementation of the GROW model. The findings indicate that the implementation of GROW-based academic supervision enhances instructional quality, particularly in lesson planning, teaching practices, and learning evaluation, while strengthening teachers’ pedagogical competence and promoting active student participation. Overall, GROW-based academic supervision proves effective as a reflective and collaborative approach to improving instructional quality in junior high schools. The study implies the necessity of sustained coaching-based academic supervision, strengthening principals’ supervisory competencies, and fostering a reflective school culture to support continuous improvement in teaching and learning quality.